2015
DOI: 10.1002/clen.201400776
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Residue Management Options Affect Crop Productivity, Weed Growth, and Soil Properties in Direct‐Seeded Fine Aromatic Rice

Abstract: Wheat residue management can influence soil health, weed growth, and productivity of subsequent rice crop. A field study was conducted to appraise the influence of different wheat residue management options viz., surface mulching of wheat residue (SMWR), wheat residue soil incorporation, wheat residue burning, zero tillage (ZT), and surface seeding on weed growth, soil physico‐chemical properties, and productivity of fine aromatic rice crop. Traditional transplanted rice (TPR) was maintained as control. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…It has been found that plant residue management can regulate the diversity and composition of the weed population by introducing qualitative and quantitative changes [138,139]. Residual CCs in the form of dead mulch change soil properties, which can impact weed control by affecting the survival, dormancy, predation, and long-term viability of weed seeds [140,141]. As dead mulch, legume CCs shade the surface of the soil and thus capture solar radiation.…”
Section: Effect Of Legume Ccs Cultivation Systems On Weed Controlmentioning
confidence: 99%
“…It has been found that plant residue management can regulate the diversity and composition of the weed population by introducing qualitative and quantitative changes [138,139]. Residual CCs in the form of dead mulch change soil properties, which can impact weed control by affecting the survival, dormancy, predation, and long-term viability of weed seeds [140,141]. As dead mulch, legume CCs shade the surface of the soil and thus capture solar radiation.…”
Section: Effect Of Legume Ccs Cultivation Systems On Weed Controlmentioning
confidence: 99%
“…The highest suppression of weeds was recorded in the wheat field as a result of sunflower residue incorporation because of the release of allelochemicals as well as the reduction of light penetration (Reberg-Horton et al, 2005;Alsaadawi et al, 2007). Crop residues may change the frequency and distribution of weeds, and they suppress weed emergence and weed growth (Essien et al, 2009;Khaliq et al, 2015). Previously, Zaji and Majd (2011) showed that the fresh and dry weights of different weeds biota viz.…”
Section: Yield Componentsmentioning
confidence: 99%
“…They provide nitrogen through release into the rhizosphere of the tested crop plant. Through the application of residues as a biological weed management strategy, it immobilizes nitrogen, which may decrease the immediate supply of nitrogen (Khaliq et al, 2015). However, at later stages of crop growth, the availability of nitrogen was enhanced through mineralization, proving that the prolonged supply of nitrogen is a continuous source of nutrition for the test crop as well as the next crops.…”
Section: Yield Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason might be the severe recourse competition inflicted by weed during the reproductive phase of the crop (Khaliq et al, 2015). Riaz et al (2006) and Khan et al (2007) have also observed less spike length when weeds were interfering with wheat crop.…”
mentioning
confidence: 99%